Accounting Standards and ESG Disclosure: Evidence from Global Banks - Annisa Fithria; Rintan Nuzul Ainy; Andreas Vernando; Nabila Na'ma Aisa; Surya Darma (InFestasi, 2026)
This study investigates the relationship between the adoption of international accounting standards and environmental, social, and governance (ESG) disclosure in the global banking sector using a panel dataset of 576 banks from 62 countries over the period 2009–2023. The empirical results show that the adoption of international accounting standards, particularly IFRS, is positively associated with ESG disclosure among global banks. Additional analyses indicate that the effect of accounting standards is stronger for environmental and social disclosure than for governance disclosure. The results also suggest that major global events, including the Paris Agreement and the COVID-19 pandemic, are associated with increased ESG disclosure. This study contributes to the literature by providing cross-country evidence on the relationship between accounting standards and ESG disclosure in the banking sector, extending prior research that primarily focuses on single-country settings. The findings highlight the broader transparency effects of international financial reporting frameworks and provide implications for regulators and policymakers seeking to strengthen sustainability reporting and promote sustainable finance.